2006
DOI: 10.1007/s10528-006-9029-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphism of Interferon-γ, Interferon-γ Receptor, and Interferon Regulatory Factor-1 Genes in Patients with Hepatitis B Virus Infection

Abstract: The natural history of hepatitis B virus (HBV) infection is probably related to host immune factors. Interferon-c (IFN-c) plays significant roles in immune defense. This study was undertaken to investigate the association between HBV infection and single nucleotide polymorphisms (SNPs) of IFN-c, IFN-c receptor (IFNGR)-1 and 2, and interferon regulatory factor (IRF)-1 genes. Between March 2002 and December 2002, 614 Korean patients were enrolled in two different groups: an HBV clearance group (n = 201), who wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
2
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 26 publications
0
27
2
1
Order By: Relevance
“…Previous reports have shown that several cytokine polymorphisms are associated with the natural history of HBV infection in Korea [22,23]. Recently, we demonstrated associations between IFN-c-related gene SNPs and HBV clearance [13]. Cytotoxic T lymphocytes may damage HBV-infected hepatocytes by releasing humoral immune mediators of inflammation such as IL-2, tumor necrosis factor (TNF)-a, and IFN-c [24].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous reports have shown that several cytokine polymorphisms are associated with the natural history of HBV infection in Korea [22,23]. Recently, we demonstrated associations between IFN-c-related gene SNPs and HBV clearance [13]. Cytotoxic T lymphocytes may damage HBV-infected hepatocytes by releasing humoral immune mediators of inflammation such as IL-2, tumor necrosis factor (TNF)-a, and IFN-c [24].…”
Section: Discussionmentioning
confidence: 98%
“…We have previously demonstrated some of the host genetic factors that are associated with HBV infection outcome in the Korean population [11][12][13]. IL-18 plays a pivotal role in inducing cytotoxic T lymphocyte response, which is important in the outcome of HBV infection; for this reason, we analyzed IL-18 single-nucleotide polymorphisms (SNPs) as potential candidates for HBV-clearance agents.…”
Section: Introductionmentioning
confidence: 99%
“…Shin et al [10] reported that IL10-ht2 (high IL-10 secretor phenotype) accelerates the progression of chronic HBV infection, especially the development of HCC in the Korean population, although the exact functional mechanisms of HCC occurrence were not clearly explained. Recently, we demonstrated an association between IFN-c-related gene SNPs and HBV outcome [13]. Cytotoxic T lymphocytes [24].…”
Section: Discussionmentioning
confidence: 99%
“…Our research group has investigated host genetic factors that are associated with HBV infection outcomes [11][12][13]. As part of our effort to identify additional SNPs in genes implicated in the outcome of HBV infection, we analyzed IL-18 SNPs as potential candidates for the development of HCC in HBVinfected individuals, and the biological relevance of the significantly associated SNP was assessed by a functional study in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…IRF1 has been shown to play roles in regulating apoptosis, tumor-suppression and DNA damage response [71,72]. Findings suggest that IRF1 is a candidate gene marker for determining patient susceptibility to the development of chronic hepatitis B and C [73,74]. Some findings indicate that a common mis-sense SNP in ATF6 may contribute to susceptibility of HCC functionally [75].…”
Section: Discussionmentioning
confidence: 99%